I dream of Jeanie (with the light brown hair) [videorecording (DVD)] - Dwan, Allan, 1885-1981; Middleton, Ray; Shirley, Bill, 1921-1989; Lawrence, Muriel, 1930-; Christy, Eileen; Allen, Rex, 1920-1999 (Digiview Productions, 2004)
The dramatized story of famed American composer Stephen Foster.